2008
DOI: 10.1093/carcin/bgn076
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inactivation of the secreted frizzled-related protein-5 ( SFRP5 ) gene in human breast cancer is associated with unfavorable prognosis

Abstract: Disruption of the Wnt pathway is thought to be crucial in the development of human cancer. Pathway inhibitory members of the secreted frizzled-related protein (SFRP) family were found to be downregulated due to epigenetic inactivation in various malignancies. To date, only SFRP1 has been studied in human breast cancer and we questioned whether other SFRP genes may be implicated in the pathogenesis of this disease as well. An initial real-time polymerase chain reaction analysis of SFRP5 expression in normal hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 45 publications
4
63
0
1
Order By: Relevance
“…Wnt ligands and FZD receptors are expressed in human breast cancer cell lines and primary tumors (30)(31)(32)(33). Multiple negative regulators of Wnt/β-catenin signaling, such as SFRP1, SFRP2, SFRP5, WIF1, DKK1, and DKK3, are down-regulated in many breast tumors (34)(35)(36)(37)(38)(39). Although Wnt/β-catenin pathway mutations are rarely detected in breast tumors, elevated levels of nuclear and/or cytoplasmic β-catenin are frequently found and are associated with poor prognosis (40).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt ligands and FZD receptors are expressed in human breast cancer cell lines and primary tumors (30)(31)(32)(33). Multiple negative regulators of Wnt/β-catenin signaling, such as SFRP1, SFRP2, SFRP5, WIF1, DKK1, and DKK3, are down-regulated in many breast tumors (34)(35)(36)(37)(38)(39). Although Wnt/β-catenin pathway mutations are rarely detected in breast tumors, elevated levels of nuclear and/or cytoplasmic β-catenin are frequently found and are associated with poor prognosis (40).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from SFRP1 and SFRP2, various studies also reported SFRP5 expression to be downregulated and epigenetically inactivated in breast cancer and this trend dictated a poor overall survival [62]. The expression of the molecule was rescued when cells were treated with DNAdemethylating drugs, confirming the methylation-based silencing of another SFRP tumour suppressor in breast cancer.…”
Section: Breast Cancermentioning
confidence: 90%
“…While none of the control samples showed hypermethylation. Veeck et al stated that hypermethylation of SFRP-1 associated with poor prognosis in breast cancer patients [20,21]. SFRP gene promoter hypermethylation has been demonstrated in different hematopoietic malignancies like acute lymphoblastic leukemia (ALL) and Multiple myeloma (MM).…”
Section: Discussionmentioning
confidence: 99%